Corporate Social Responsibility of Five-Star Hotels in Bali - I Gusti Ayu Intan Saputra Rini; Muhammad Asyraf Hasim; Luh Kade Datrini (Jurnal Ilmiah Akuntansi, 2022)
This study aims at describing the CSR of five-star hotels in Bali, analyze the perceptions of the surrounding community towards hotel CSR and provide recommendations for CSR strategies for hotels based on the GRI Standards and local community perceptions. Respondent samples were selected using purposive sampling and data in the study were collected using interviews, documentation and questionnaires. This study uses an interactive model of qualitative data analysis techniques. The results of the study prove that: for the CSR the five-star hotels in Bali do not have an autonomous sector and do not have their own budgetary authority. Five-star hotels in Bali have also not reported their own CSR activities in the sustainability report. CSR activities of the hotels are mostly in the form of donations (philanthropy). 29% of the CSR activities of the hotels are perceived as low by the surrounding community, and in the end, this research is able to produce several recommendations for CSR management strategies for five-star hotels in Bali.